Seize the present day: TikTok entertainment content and youth satisfaction / Siti Mardhiyyah Mohd Fauzi … [et al.] - Mohd Fauzi, Siti Mardhiyyah; Hayat Adnan, Wardatul; Khamis, Mohd. Fadly; Ibnu, Ireena Nasiha; Mazlan, Nurul Hijja (Faculty of Communication and Media Studies (FCMS), 2023)
In September 2016, TikTok entered the social media industry and quickly established itself as the dominant force in the world of social sharing. TikTok content is completely based on user needs, increasing video types and high video quality, in line with the characteristics of different users, and therefore increasing user interaction, especially entertainment content. This paper aims to study the effect of entertainment content on TikTok users’ satisfaction among youth in Klang Valley, Peninsular Malaysia. This study is based on quantitative data gathered from an online questionnaire that inquired about 431 respondents in the Klang Valley about the influences and effects of entertainment content. The data was analysed using descriptive analysis and hypothesis testing. The findings showed that the Pearson correlation Coefficient relationship between the effect of TikTok entertainment content and youth satisfaction significantly was found to be significantly strong and positive. The research suggested that innovating and increasing content quality by encouraging User Generated Content (UGC) and expressing content variety to target audiences. TikTok should implement a time management system in which, if a user’s online time exceeds a certain threshold, an alert window will immediately appear to ensure healthy browsing and avoid indulging.